1939
DOI: 10.1063/1.1707343
|View full text |Cite
|
Sign up to set email alerts
|

An X-Ray Investigation of Crystallinity in Rubber

Abstract: X-ray diffraction evidence has shown that a crystalline structure can be produced in rubber by stretching or by freezing. In the former case, a fiber diagram is generally secured, in the latter, Debye-Scherrer rings. When raw rubber was stretched to moderate elongations and frozen an intense fiber diagram was found, showing that the crystallization proceeded from nuclei set up by the stretching. A series of diffraction patterns illustrating the effect are reproduced. The geometrical conditions of stretching un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1951
1951
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…These authors pointed out that vulcanization of rubber does not affect its ability to crystallize. The diffraction patterns of vulcanized and unvulcanized NR are very similar as shown in the work of Gehman and Field,31 who also demonstrated that the crystal structure is not changed in NR vulcanizates containing carbon black fillers. 32 The influence of crosslinking and fillers on SIC will be detailed in Section IV of the present article.…”
Section: The Crystalline Phase Of Natural Rubber a Crystallograpsupporting
confidence: 61%
See 1 more Smart Citation
“…These authors pointed out that vulcanization of rubber does not affect its ability to crystallize. The diffraction patterns of vulcanized and unvulcanized NR are very similar as shown in the work of Gehman and Field,31 who also demonstrated that the crystal structure is not changed in NR vulcanizates containing carbon black fillers. 32 The influence of crosslinking and fillers on SIC will be detailed in Section IV of the present article.…”
Section: The Crystalline Phase Of Natural Rubber a Crystallograpsupporting
confidence: 61%
“…31 Nevertheless, if crystallites appear to be more oriented with the stretch (and also with the time), their size seems to remain constant. 30 This last point is very important and was already suggested in 1926 by Hauser and Mark 62 who noticed that the "half-value width" of the spots did not change appreciably with stretch; consequently, these authors considered that the increase of crystallinity is explained by an increase in the number of crystallites rather than by an increase of their size.…”
Section: B Crystallinity Versus Stretch Ratiomentioning
confidence: 99%
“…A fully developed spherulitic texture is, however, not recognized in Figure 4(b) though binocularly developed twodimensional spherulites were clearly observed in the film fully crystallized under no strain in ref 9. The greater population density of crystallization nuclei (possibly, heterogeneous nuclei) and thereby less space for the sheaves (namely, immature spherulites) to mature in our case is deduced to be a probable reason, 21 because the size of the sheaves in Figure 4 Shorter crystallization time (7 h) in our experiment than that (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) h) in ref 9 might be another reason. The identity of the B-domains is not established in the present study.…”
Section: Polychloroprene ( Cr)mentioning
confidence: 72%
“…Strain-induced crystallization was first studied by an X-ray diffraction method by Gehman and Field. [1] For several decades in the 20th century, research on rubber science was deeply developed. [2,3] The NR crystal structures, as well as lattice constants, were reported by Mark and von Susick, [4] Morss, [5] and Bunn [6] based on wide angle X-ray diffraction (WAXD).…”
Section: Introductionmentioning
confidence: 99%